2005
DOI: 10.1111/j.1365-294x.2005.02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen flow in the wildservice tree, Sorbus torminalis (L.) Crantz. II. Pollen dispersal and heterogeneity in mating success inferred from parent–offspring analysis

Abstract: Knowing the extent of gene movements from parents to offspring is essential to understand the potential of a species to adapt rapidly to a changing environment, and to design appropriate conservation strategies. In this study, we develop a nonlinear statistical model to jointly estimate the pollen dispersal kernel and the heterogeneity in fecundity among phenotypically or environmentally defined groups of males. This model uses genotype data from a sample of fruiting plants, a sample of seeds harvested on each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
278
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(297 citation statements)
references
References 42 publications
10
278
3
6
Order By: Relevance
“…This finding agrees with a general pattern of pollen dispersal in wind‐pollinated plants (Gerber et al., 2014; Levin & Kerster, 1974; Oddou‐Muratorio, Klein, & Austerlitz, 2005). This fat‐tailed distribution may be due to the position effect that a higher release point allows more horizontal movement and also the aerodynamic property that wind speed and turbulent flow are greater at a higher position where horizontal movement of pollen is favored (Burd & Allen, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a general pattern of pollen dispersal in wind‐pollinated plants (Gerber et al., 2014; Levin & Kerster, 1974; Oddou‐Muratorio, Klein, & Austerlitz, 2005). This fat‐tailed distribution may be due to the position effect that a higher release point allows more horizontal movement and also the aerodynamic property that wind speed and turbulent flow are greater at a higher position where horizontal movement of pollen is favored (Burd & Allen, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Schoen and Brown (1991) found N e estimates for tree species in the range of other outbreeding plants: mean values around 3,000 for Pseudotsuga menziesii and >8,000 for Pinus sylvestris and Picea abies, with high variations among populations within each species. However, locally, seed and pollen contributions to reproduction are highly uneven among individuals (Burczyk et al 2002;Krouchi et al 2004;Oddou-Muratorio et al 2005), and the great majority of the pollen disperses only in the close neighbourhood, which can greatly reduce the effective population size. In their review, Smouse and Sork (2004) found that the effective pollen pool size N ep , defined as the inverse of the probability that a female draws two offsprings from the same father, ranges from 2 to 200 in tree populations.…”
Section: Random Changes Due To Genetic Drift and Mating Systemmentioning
confidence: 99%
“…Using this approach in Quercus suber, Ramirez-Valiente et al (2011) detected significant heritability but nonsignificant selection gradient for carbon isotope discrimination, contrasting with very low heritability and significant selection gradient for specific leaf area. An alternative approach of selection gradients through the assessment of actual reproductive success in situ was recently developed (Oddou-Muratorio et al 2005;Burczyk et al 2006;Klein et al 2011). This method, based on the mixed-mating neighbourhood model, consists in estimating the reproductive success of individual adult trees using spatial genetic data of seedlings and their potential parents and then in relating this reproductive success to phenotypic traits.…”
Section: What Is New In Molecular and Phenotypic Tools?mentioning
confidence: 99%
“…Parameters of pollen dispersal and male fecundity have often been estimated on the basis of the neighborhood model using maximum likelihood (Burczyk et al, 2002) or Bayesian methods (Klein et al, 2008). In our mating model, the results of paternity assignment were used to simplify the model (Tani et al, 2009), and an exponential power function (Oddou-Muratorio et al, 2005) was applied to a dispersal kernel. Based on the paternity assignment, mother trees with 410 seeds, whose pollen donors were found within the plots, were examined in our model.…”
Section: Effects Of Si On Mating Successmentioning
confidence: 99%